CD2 targeted nanoparticles containing IL-2 mimic fetal-maternal tolerance of pregnancy by inducing synergistic TGF-β-producing NK cells and Tregs - Horwitz, David A.; La Cava, Antonio (Frontiers in Immunology, 2025)
T regulatory cells (Tregs) are essential for maintaining immune homeostasis and tolerance. We have reported that CD2-targeted nanoparticles containing IL-2 induce CD4 and CD8 Foxp3+ Tregs, together with TGF-β-producing CD56bright NK cells. Generation and maintenance of stable Tregs critically depended on TGF-β dependent interactions between these adaptive and innate immune cells. This resembles what occurs in maternal-fetal tolerance in pregnancy, where TGF-β from uterine stromal cells and fetal trophoblasts induces NK cells and T cells to become decidual Tregs and NK cells that prevent fetal rejection. Thus, both in the periphery and in utero, a TGF-dependent crosstalk between NK cells and Tregs appears vital for maintaining immune tolerance. This mimicry of maternal-fetal tolerance has clinical relevance. Subjects with SLE and other autoimmune disorders have deficits in IL-2, TGF-β and NK cells. It is likely that recent clinical trials in these diseases with IL-2 that did not reach their primary end points because they failed to address these additional defects. Our anti-CD2 conjugated NPs target CD2-bearing T cells and NK cells and provide them with IL-2 and TGF-β in vivo in order to repair both cytokine defects. Moreover, the NPs do not need to be encapsulated with TGF-β because the NK cell-derived TGF-β produced locally by the target cells is sufficient to sustain Tregs. For these reasons, we believe this NP platform has great potential not only for the prevention and/or treatment of a wide variety of immune-mediated disorders, but also to prevent recurrent miscarriages.